Comparative study on the dye sensitized solar cell performance of solution processed ZnO - Jana, Arpita; Das, Partha Pratim; Agarkar, Shruti A.; Devi, P. Sujatha (Solar Energy, 2014)
We have monitored the performance of the dye-sensitized solar cells (DSSC) using solution processed ZnO having different shapes and aspect ratios. The aspect ratio and surface area of the ZnO structures have been regulated by carefully controlling the precursor concentration and reaction conditions. The shape of the synthesized structures has been varied from larger rods to smaller rods to hexagonal prisms. The synthesized hexagonal prism shaped ZnO with an aspect ratio of around one exhibited the highest surface area of 42 m(2)/g. The ZnO rods with higher aspect ratios of 5 and 16 exhibited lower surface areas of 22 and 2 m(2)/g, respectively. The dye sensitized solar cells constructed using the as-prepared ZnO structures and N719 dye molecules, exhibited efficiencies that varied as a function of surface area of the samples, with ZnO hexagonal prism exhibiting a maximum efficiency of around 1.38 +/- 0.01%. The results indicated a direct correlation between the surface area of the ZnO structures and the energy conversion efficiency. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: DSSC; Photoanode; surface area; ZnO

Defects in chemically synthesized and thermally processed ZnO nanorods: implications for active layer properties in dye-sensitized solar cells - Das, Partha Pratim; Agarkar, Shruti A.; Mukhopadhyay, Soumita; Manju, Unnikrishnan; Ogale, Satishchandra B.; Devi, P. Sujatha (Inorganic Chemistry, 2014)
We have carried out the effect of post annealing temperatures on the performance of solution-grown ZnO rods as photoanodes in dye-sensitized solar cells. Keeping our basic objective of exploring the effect of native defects on the performance of DSSC, we have synthesized ZnO rods having length in the range of 2-5 mu m by a modified sonication-induced precipitation technique. We performed extensive characterization on the samples annealed at various temperatures and confirmed that annealing at 300 degrees C results in ZnO rods with minimum native defects that have been identified as doubly ionized oxygen vacancies. The electron paramagnetic resonance measurements on the samples, on the other hand, confirmed the presence of shallow donors in the low temperature annealed samples. We also carried out electrochemical impedance measurements to understand the transport properties at different interfaces in the solar cell assembly. We could conclude that solution-processed ZnO rods annealed at 300 degrees C are better suited for fabricating DSSC with improved efficiency (1.57%), current density (5.11 mA/cm(2)), and fill factor (45.29%). On the basis of our results, we were able to establish a close connection between the defects in the metal oxide electron transporting nano system and the DSSC performance.

Photochemical performance of ZnO nanostructures in dye sensitized solar cells - Das, Partha Pratim; Mukhopadhyay, Soumita; Agarkar, Shruti A.; Jana, Arpita; Devi, P. Sujatha (Solid State Sciences, 2015)
In this work, the photoconversion efficiencies of ZnO having diverse microstructures and structural defects have been investigated. A conversion efficiency of 138% was achieved for the DSSCs fabricated with as prepared ZnO nanorods having minimum vacancy defects and a favourable one dimensional directional pathway for electron conduction. The DSSCs fabricated with ZnO nanoparticles exhibited relatively low conversion efficiency of 1.004% probably due to multiple trapping/detrapping phenomena within the grain boundaries and ZnO flowers though exhibited a high dye adsorption capability exhibited the lowest conversion efficiency of 0.59% due to a high concentration of structural defects. Based on the experimental evidences, we believe that the type of defects and their concentrations are more important than shape in controlling the overall performance of ZnO based DSSCs. (C) 2015 Elsevier Masson SAS. All rights reserved.
Keywords: DSSC; Efficiency; Emission; Structural defects; ZnO

Performance of colloidal CdS sensitized solar cells with ZnO nanorods/nanoparticles - Roy, Anurag; Das, Partha Pratim; Tathavadekar, Mukta; Das, Sumita; Devi, Parukuttyamma Sujatha (Beilstein Journal of Nanotechnology, 2017)
As an alternative photosensitizer in dye-sensitized solar cells, bovine serum albumin (BSA) (a nonhazardous protein) was used in the synthesis of colloidal CdS nanoparticles (NPs). This system has been employed to replace the commonly used N719 dye molecule. Various nanostructured forms of ZnO, namely, nanorod and nanoparticle-based photoanodes, have been sensitized with colloidal CdS NPs to evaluate their effective performance towards quantum dot sensitized solar cells (QDSSCs). A polysulphide (S-x(2-))-based electrolyte and CuxS counter electrode were used for cell fabrication and testing. An interesting improvement in the performance of the device by imposing nanorods as a scattering layer on a particle layer has been observed. As a consequence, a maximum conversion efficiency of 1.06% with an open-circuit voltage (V-OC) of 0.67 V was achieved for the ZnO nanorod/nanoparticle assembled structure. The introduction of ZnO nanorods over the nanoparticle led to a significant enhancement of the overall efficiency compared to the corresponding bare nanoparticles.

Hydrothermally synthesized fluorescent Zn2SnO4 nanoparticles for dye sensitized solar cells - Das, Partha Pratim; Roy, Anurag; Agarkar, Shruti; Devi, Parukuttyamma Sujatha (Dyes and Pigments, 2018)
In this work, we have investigated the interaction of hydrothermally synthesized Zn2SnO4 (ZTO) nanoparticles (NPs) with two different commercial photo sensitizers such as N719 and N3 dye molecules and studied their performance in dye sensitized solar cells (DSSC). Interestingly, the ZTO NPs exhibited band edge emission in the mid UVA region and as a result possibility of enhanced light harvesting in the terminal UVA region was anticipated in the device due to the efficient energy transfer observed in case of the sensitizer N719 than N3. The dye sensitization property has been found to be higher for the N3 dye molecules than the N719 dye molecules as based on the time dependent dye loading study. The devices fabricated with ZTO-N719 exhibited improved photovoltaic performance compared to the ZTO-N3 based devices exhibiting an overall conversion efficiency of 2.56% by the former compared to the later (1.90%) under 1SUN 1.5AM illumination and sensitization for 12 h.